Lived experiences of recovered COVID-19 patients after hospitalization: A phenomenological research - Mojtaba Fattahi Ardakani; Tahmineh Farajkhoda; Akram Mehrabbeik (Wolters Kluwer Medknow Publications, 2022)
Background: The deadly novel Coronavirus Disease 19 (COVID-19) epidemic has sickened and killed millions of people around the world. Accordingly, Iran has had the second highest incidence rate of COVID-19 deaths in the world. Because this disease affects all individual, familial, and social aspects, there is not enough information about experiences of COVID-19 patients. However, these experiences could be a missing link in explaining their attitudes, beliefs, and concerns for improving care and treatment processes during and after the disease. Materials and Methods: Descriptive phenomenological research was conducted in 2020 to explain experiences of 21 COVID-19 patients after post-hospitalization recovery. Semi-structured interviews were used as the data collection tool via purposeful sampling, which were continued until data saturation and analyzed using Colaizzi's seven-step method. Results: The main theme of "value of health" and the seven categories of (1) inefficient self-care, (2) overcoming the catastrophic crisis, (3) the shadow of death, (4) coping behaviors and resilience, (5) the need for support and accountability, (6) sympathy, and (7) new insights as well as 38 main codes were extracted. The patients' general explanation in the early stages of the disease, recovery, and subsequent periods included transition from the crisis to new insights into physical, mental, sexual, familial, and economic dimensions that finally led to the review value and concept of their life. Conclusions: The findings of this study can be used to fulfil care and treatment needs of the patients, their families as well as caregivers, psychologists, counselors, health planners, and managers presently and in the future for similar diseases.